Intracystic hemorrhage in a mediastinal cystic adenoma causing parathyrotoxic crisis. - Manouras, Andreas; Toutouzas, Konstantinos G; Markogiannakis, Haridimos; Lagoudianakis, Emmanuel; Papadima, Artemis; Antonakis, Pantelis T; Kafiri, Georgia; Bramis, Ioannis (Head Neck, 2008)
BACKGROUND: We report a case of intracystic hemorrhage in a mediastinal cystic parathyroid adenoma causing parathyrotoxic crisis. METHODS AND RESULTS: A 30-year-old man presented with a large neck mass, dyspnea, and abdominal pain. The patient's serum calcium and parathormone levels were elevated. Radiography showed a right tracheal deviation, ultrasonography identified a thyroid nodular goiter extending to the mediastinum with a large (4.0 cm x 5.6 cm) cystic mass adjacent to the lower left thyroid pole. After IV fluid, pamidronate, and furosemide were administered, the patient underwent total thyroidectomy, and excision of the cyst and a small mass (2 cm x 2 cm) adjacent to the upper right thyroid lobe. Histopathologic examination revealed a double parathyroid adenoma and identified the mediastinal lesion as a cystic adenoma with intracystic hemorrhage. CONCLUSIONS: Intracystic hemorrhage in a functional mediastinal cystic parathyroid adenoma is an extremely rare cause of parathyrotoxic crisis. Aggressive medical treatment should be immediately instituted, and surgery should be performed as soon as hypercalcemia is controlled.
Keywords: Adenoma; Adult; Bone Density Conservation Agents; Cystadenoma; Diphosphonates; Diuretics; Fluid Therapy; Furosemide; Hemorrhage; Humans; Hypercalcemia; Hyperparathyroidism; Male; Mediastinal Neoplasms; Pamidronate; Parathyroid Neoplasms; Thyroid Crisis; Thyroidectomy